Mulkeeragh road sign - Frank Ferguson:::Creator:::::::::::: (United Kingdom; Ballykelly, Londonderry, Northern Ireland, 2023)
Road sign for Mulkeeragh (Mul-caerach) is a townland in Ballykelly, County Londonderry, Ireland. John Steinbeck's ancestral home place in Ireland. Steinbeck's trip to Ireland in the summer of 1952 did not yield the extensive evidence for the lineage of his family he had hoped to find. Photograph appears in Steinbeck Review, vol.16, no.2, 2022.